HOW IS A WETLAND ADMINISTERED? DISCUSSING THE GEDIZ DELTA FROM ECOLOGICAL PERSPECTIVE. - ÇELİK, Mehmet Ali; ÜNAL, Çiğdem (Electronic Turkish Studies)
Wetlands have a great importance for its containing biological diversity and continuity of ecological balance. Turkey is rich in wetlands and also of a strategical importance on international level. From this perspective, it is important for current wetlands to get survived both ecologically and economically. Main motivation of this study is to reach to reply the question ‘Are sufficient planning and protection measures being taken in our country?' For this purpose, we chose Gediz Delta as study area, which embodies a wide variety of bird and living creature species, and is a wetland with a class-A importance, and we examined relationship between land cover change and economic activities around Gediz Delta. Findings obtained show that large organized industry facilities were also established around Gediz Delta where agricultural activities are intensively being performed. According to Landsat data belonging to the years of 1984-2000 and 2015, it was determined that marsh in wetland was transformed, by draining, into agricultural cultivated area, We saw marsh land existed on Landsat TM image belonging to 1984, while there was no marsh land on the image belonging to 2000 and 2015. At the same time, Atatürk Organized Industrial Site (AOSB) which had been established on 10km due east of the wetland increased anthropological pressure on wetland. Based on construction of the said Industrial Site, cultural landscape has begun to take the place of natural landscape around Gediz Delta. Data obtained reveal that wetland of Gediz Delta is not being administered well, and results obtained from satellite images put forth that the construction of AOSB in particular generated important changes around the wetland.